GENE POLYMORPHISM IN ASSOCIATION WITH ATHEROSCLEROSIS DEVELOPMENT AND COGNITION DISORDERS IN PATIENTS WITH ISCHEMIC CHRONIC HEART FAILURE - T. V. Martynovich; N. S. Akimova; E. A. Fedotov; Yu. G. Shvarts (Кардиоваскулярная терапия и профилактика)
Aim. To study the interrelation of polymorphic gene variants playing role in atherosclerosis development, with cognition disorders, central nervous system condition and chronic heart failure (CHF) course specifics in patients with ischemic heart disease. Material and methods. 40 patients with CHF I-IV functional class (NYHA) of ischemic origin underwent cognition testing, nuclear-magnetic resonance tomography of the brain, duplex brachiocephalic arteries scanning, gene APOC3, ABCA1 и PON1 polymorphism assessment, and lipid, homocystein, brain natriuretic peptide measurement (BNP). Results. The interrelations of polymorphic gene variants APOC3, ABCA1 и PON1 were found with morphological changes in the brain and cognition tests results. T allele at PON1 (polymorphism L55M A>T) and allele A at PON1 (polymorphism Q192R A>G) associated with the worsening of Burdone correction test, and T allele of APOC3 gene (polymorphism -482C>T) was linked to the decrease of diffusion coefficients in gray as in white matters. There are statistically significant relations of the polymorphisms studied with the levels of plasma lipids, homocysteine and carotid arteries diameter and intima-media complex thickness. While studying relations of polymorphic genes ABCA1 и APOC3 variants (C3238G) and CHF duration, BNP level and end- systolic size of the left atrium it was found that the allele A of gene ABCA1 and allele G of gene APOC3 ^3238G) are associated with longer duration of CHF. The increase of the left atrium size and higher BNP levels were shown in patients — carriers of C allele gene APOC3 (polymorphism -428 C>T).Conclusion. There is interrelation of gene polymorphism that are associated with lipid metabolism disorders, CHF course and cognition functioning and morphological changes in central nervous system in CHD patients.